Mind the gap – Small bowel obstruction due to preperitoneal herniation following laparoscopic inguinal hernia repair – A case report. (November 2021) - Thalheimer, Andreas; Vonlanthen, Rene; Ivanova, Silviya; Stoupis, Christoforos; Bueter, Marco
Abstract: Introduction and importance: Inguinal hernia repair is a very frequent operation in general and visceral surgery worldwide. The laparo-endoscopic approaches such as TAPP have gained increasing acceptance among specialists and many consider them as standard of care due to perioperative safety and excellent postoperative results. Knowledge of specific complications after minimally invasive inguinal hernia surgery, however, is important for the successful management of these patients. Case presentation: We herein present the case of a 75-year-old female patient who electively underwent laparoscopic repair of combined inguinal and femoral hernia. During the postoperative course a small bowel obstruction occurred requiring emergency re-laparoscopy revealing a preperitoneal herniation of small bowel through a peritoneal defect. Clinical discussion: Small bowel obstruction due to preperitoneal herniation of small bowel through a peritoneal defect after laparoscopic hernia repair is extremely rare. In such cases, emergency laparoscopic revision is necessary to avoid bowel ischaemia. Adequate closure of the peritoneum during the primary procedure along with the necessary attention to detail seems mandatory to avoid preperitoneal herniation after TAPP. Conclusion: Inadequate peritoneal closure after TAPP may lead to preperitoneal herniation of the small bowel leading to postoperative intestinal obstruction. All hernia surgeons should be aware of this rare, but potentially life-threatening complication and should close all peritoneal defects with greatest care and accuracy. Highlights: Laparoendoscopic techniques are standard treatment for inguinal hernia repair Specific complications due to the intraabdominal approach can occur in laparoscopic TAPP Herniation of small bowel through peritoneal gaps following laparoscopic TAPP can cause serious postoperative complication The early detection of this complication is important to avoid a threatening postoperative course Careful closure of all peritoneal gaps is critical to avoid preperitoneal herniation